Inovasi Strategi Pembelajaran Pendidikan Agama Islam Berbasis Brain Based Learning di SMK Muhammadiyah 1 Temon - Wahyudi, Nanang; Widodo, Hendro (TADRIS: Jurnal Pendidikan Islam, 2020)
The purpose of this study is to describe the role of brain based learning models in Islamic religious education so that the values of Islamic religious education can be applied in everyday life. The research method used is descriptive research using a qualitative approach. Data collection techniques with interviews and observations.The data analysis technique used is phenemenological analysis which is a technique for drawing conclusions based on the data obtained and in accordance with the research objectives. The results of this study are learning conducted with a brain based learning model to provide optimal results, students are more aware of the learning process and have a positive impact on everyday life. Â Â